Antidiarrhoeal Activity of Aqueous Leaf Extract of Momordica Spp. (CUCURBITACEAE): Evaluation of the inhibitory effect of aqueous leaf extract of Momordica spp. on diarrhea and gastrointestinal function (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Antidiarrhoeal activity of aqueous leaf extract of Momordica charantia (CUCURBITACEAE) wasevaluated on castor oil induced diarrhea, gastro-intestinal transit, intestinal fluid accumulation andgastric emptying in mice. The aqueous extract of its leaves showed inhibitory activity against castor oilinduced diarrhoea. Inhibition of the gastrointestinal population and fluid secretion by the extract suggestthat the existing extract exert the anti-diarrhoeal activity by anti-secretory mechanism.